HUBUNGAN KARAKTERISTIK WIRAUSAHA DENGAN KOMPETENSI KEWIRAUSAHAAN PETERNAK SAPI PERAH DI KABUPATEN BOGOR - Yustika Muharastri; Rachmat Pambudy; Wahyu Budi Priatna (University of Jember, 2015)
Entrepreneurship has a positive relationship with economic growth in a country since its role in the economic growth which absorbs local resources and creates jobs. Livestock subsector is one of parts of agricultural sector which has good opportunity to be developed because the national market demand of milk product is still high. Bogor Regency is one area in West Java which has dairy cow industry. Nevertheless, dairy farmers in Bogor have not been optimally developed the potential opportunities in dairy farm business through entrepreneurial activities. This study aims to (1) analyse the entrepreneurial characteristics and entrepreneurial competences of dairy farmers, (2) analyse the relationship between entrepreneurial characteristics and entrepreneurial competences. The research objectives were analysed using descriptive qualitative analysis and quantitative analysis with Kendall Tau test. The result shows that the level of entrepreneurial characteristic and entrepreneurial competences of dairy farmers are low. The entrepreneurial characteristics and entrepreneurial competences also has a positive strong adequate relationship. It shows that to increase entrepreneurial competences of dairy farmers, entrepreneurial characteristics are also should bedeveloped. The government role is needed in increasing materials in training for dairy farmers to increase entrepreneurial competences and government policy to set a good milk price is also needed to give a better incentive for dairy farmers. Keywords: entrepreneur characteristic, entrepeneurial competence, dairy farmer